Financial geography – in search of a spatial dimension in finance - Paweł Węgrzyn (Ekonomista)
In the face of the growing complexity of financial markets, financial geography is gaining importance as a growing scientific sub-discipline that offers new perspectives in analysing spatial and financial processes. The purpose of this paper is to identify existing and potential future research directions in financial geography, with an emphasis on its research and application potential. Using a review of the literature supplemented by bibliometric analysis based on publications from the Scopus database, the main areas of previous research in financial geography were identified, emphasising its importance for understanding the dynamics of financial market development. New potential research areas for financial geography were also identified, focusing on sustainable development, advanced technologies and rising geopolitical tensions. Identifying these areas highlights the interdisciplinary nature of financial geography and its ability to adapt and respond to global challenges.